2022
DOI: 10.3390/molecules28010198
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Prevents Oxidative Stress and Inflammation in LPS-Induced Liver Injury through the Regulation of LncRNA-mRNA in Male Mice

Abstract: Inflammation accompanies hepatic dysfunction resulting from tissue oxidative damage. Naringenin (Nar), a natural flavanone, has known antioxidant and anti-inflammatory activities, but its mechanism of action in the regulation of liver dysfunction requires further investigation. In this study, the role of naringenin in lipopolysaccharide (LPS)-induced hepatic oxidative stress and inflammation was explored, as well as its mechanism by transcriptome sequencing. The results indicated that compared with the LPS gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…There was a dose-dependent modulation in the expression of the above-mentioned genes and proteins in the rats with PAC-induced liver injury after treatment with F100 (100 mg/kg), F200 (200 mg/kg), and F500 (500 mg/kg). Previously, it was reported that liver inflammation is a sign of almost all liver disease and a major contributor to liver damage, and PAC toxicity causes damage to the liver's central lobule region, which results in the release of reactive oxygen species (ROS) and the generation of proinflammatory cytokines [1]. The biological system includes two categories of free radicals: reactive oxygen species (ROS) that are derived from O 2 metabolism and reactive nitrogen species (RNS) that are derived from nitric oxide and superoxide [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a dose-dependent modulation in the expression of the above-mentioned genes and proteins in the rats with PAC-induced liver injury after treatment with F100 (100 mg/kg), F200 (200 mg/kg), and F500 (500 mg/kg). Previously, it was reported that liver inflammation is a sign of almost all liver disease and a major contributor to liver damage, and PAC toxicity causes damage to the liver's central lobule region, which results in the release of reactive oxygen species (ROS) and the generation of proinflammatory cytokines [1]. The biological system includes two categories of free radicals: reactive oxygen species (ROS) that are derived from O 2 metabolism and reactive nitrogen species (RNS) that are derived from nitric oxide and superoxide [31].…”
Section: Discussionmentioning
confidence: 99%
“…The liver plays a crucial role in the homeostasis maintenance of the human body. Liver damage is linked to oxidative stress and the immune system's inflammatory response [1]. Detoxification, metabolism, protein synthesis, host defense, and immunological response are just some of the many essential functions maintained by the liver [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vitro ethanol or inflammation modeling and subsequent cell experiments, the AML-12 cells were cultured in DMEM-F12, and then subjected to ethanol (500 mM) [ 33 ] or LPS (100 ng.mL −1 ) [ 34 ] with or without the addition of DMSO (0.1%), CC (10 μM), and the ELG at specified concentrations for 24 h.…”
Section: Methodsmentioning
confidence: 99%